Analysis Of Protein And Bioactivity Of Nike Fish (Awaous melanocephalus) Extract As Antioxidant - Yayurulia Hadju; Yuszda K Salimi; Nurhayati Bialangi; Netty Ino Ischak (Jambura Fish Processing Journal, 2022)
This study aims to determine the protein content and activity of nike fish (Awaous melanocephalus)  extract as an antioxidant. Nike fish (amphidromous goby larva) is an endemic fish of Gorontalo which is consumed as food and contains minerals, fats, carbohydrates, amino acids, and high protein. Nike fish extract uses a buffer with several components such as water, Tris HCl 0.1 M pH 8.3, NaCl 2 M, CaCl 0.01 M, 2-Mercaptoethanol 1%, and Triton X-100 0.5%. Based on qualitative analysis, Nike fish protein extract was positive through biuret, ninhydrin, xantoproteate, and Pb sulfide tests. Judging from the quantitative analysis, nike fish extract using the biuret method using UV VIS and TVB-N spectrophotometers obtained 47.60% and 0.098%, respectively. The antioxidant activity of nike fish extract using the DPPH method (1,1-diphenyl-2-pycryhydrazyl) was 20.29 mg AEAC/g (Ascorbic acid Equivalent Antioxidant Capacity). IC50 (Inhibitory Concentration) is 520 ppm at low levels but has potential as an antioxidant.